Evaluation of User Experience and Sociability on Platforms of Ephemeral Narratives: an Instagram Stories Case Study - Silva, Thiago A. de S.; Barbosa, Glívia A. R.; Santana, Ismael S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2018: Proceedings of the 24th Brazilian Symposium on Multimedia and the Web, 2018)
This work aimed to characterize how Instagram Stories supports the sociability among its members and to discuss the impact of this proposed sociability in the social interaction of users. We conducted this research in three steps. First, we executed an evaluation in a perspective of Human-Computer Interaction (HCI) experts, which aimed to analyze whether the features offered by Instagram Stories are adequate to user experience (UX) and sociability guidelines. Next, we performed an evaluation from the users' perspective, in order to investigate users' experience while they are interacting through Instagram Stories. Finally, we made a triangulation of the results and we discussed the impact of Instagram Stories in the social interaction of users. The results showed that the interface and interaction model of Instagram Stories reflects directly on the experience of use and sociability of its members. As contributions, we present recommendations and insights to HCI community about the design and evaluation of ephemeral communication services.